Menghajikan Anak yang Belum Baligh Perspektif Imam Hanafi dan Imam Asy-Syafi’i (Studi Kasus di Kecamatan Medan Marelan) - Afsari, Rafika Hidayah; Syam, Syafruddin; Akbar, Ali (Asian Journal of Early Childhood and Elementary Education, 2023)
Issues relating to the Hajj in Indonesia are still an issue that is discussed, considering that the Hajj itself is a form of worship or the fifth pillar of Islam. In the sense that Islam is perfect if you have completed the Hajj pilgrimage, however, the departure for the Hajj pilgrimage is only for the community (only capable Muslims) and is not a necessity if you do not have the ability. This type of research is empirical sociological research. The nature of the research in this research is comparative. Comparative Research is research that is comparative in nature, which is compared in the form of similarities or differences. In this research, those who will be compared are Imam Hanafi and Imam Asy-Shafi'i. The author found 2 cases in Medan Marelan District where parents had made their children Hajj (registered their children to be able to perform the Hajj) because their children had not yet reached puberty. Namely the family of Mr Suharjo Suhartono and the family of Mr Muhammad Zainal. Mr. Suharjo Suhartono has registered his 9 year old son, Farhan Agus Mumtaza, to be able to go on the Hajj later. Meanwhile, Mr. Muhammad Zainal also did the same thing, namely registering his son, Muhammad Rizqon Febriansyah, aged 12 years to go on the Hajj later. This difference is due to the propositions they use, Imam Hanafi uses general propositions, while Imam Asy-Shafi'i uses specific propositions. While their opinion regarding the condition of a child who has not reached puberty and has been registered for Hajj is that this depends on the ability of the individual (his family), Imam Hanafi is of the opinion that istitha'ah (ability) depends on health and material capabilities. Meanwhile, for Imam Asy-Syafi'i, it only depends on material capabilities. Therefore, in this case their opinions complement each other.